2011
DOI: 10.1002/csr.284
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Socio‐demographic Variables and Concerns about Environmental Sustainability

Abstract: Researchers have studied many variables to understand consumer behavior and the choices consumers make, with regard to environmentally friendly products. Past research has tried to find the relationships between socio-demographic variables and preferences for environmentally sustainable products. The findings, however, are still relatively mixed, especially those concerning income; previous results are far from being conclusive in that past studies have found income to be negatively, positively, and insignific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 33 publications
2
45
0
2
Order By: Relevance
“…The renewed interest in the area of green marketing has generated new perspectives in the literature from both organizational and consumer perspectives (Chen and Chang, ; Lee et al , ; Park et al , ). In order to expand the existing literature, this study proposed and tested an integrated model examining the effect of consumers' concern for environmental values and their general attitudes towards green products on green brand image and its subsequent influence on green brand trust and green brand equity.…”
Section: Discussionmentioning
confidence: 99%
“…The renewed interest in the area of green marketing has generated new perspectives in the literature from both organizational and consumer perspectives (Chen and Chang, ; Lee et al , ; Park et al , ). In order to expand the existing literature, this study proposed and tested an integrated model examining the effect of consumers' concern for environmental values and their general attitudes towards green products on green brand image and its subsequent influence on green brand trust and green brand equity.…”
Section: Discussionmentioning
confidence: 99%
“…Lin and Huang, 2012;Urien and Kilbourne, 2011;Vermeir and Verbeke, 2008) and socio-demographic characteristics (e.g. do Paço and Raposo, 2009;Park et al, 2012) as the most often considered determinants. Attitude and values turn out to be better predictors than socio-demographic characteristics, with the latter showing contradictory findings (Diamantopoulos et al, 2003;DiazRainey and Ashton, 2011;Rex and Baumann, 2007;Zhao et al, 2014).…”
Section: Consumers' Green Purchasing Behaviourmentioning
confidence: 99%
“…Following the studies on CSR in general, some researchers found that women have a more protective attitude towards the environment in particular (Wehrmeyer & McNeil, 2000) and are more likely than males to be ecologically conscious (Park, Choi, & Kim, 2012). Related research shows that boards with a higher proportion of women directors had higher environmental performance (Kassinis et al, 2016;Li et al, 2017;Lu & Herremans, 2019;Post et al, 2015;Walls et al, 2012) and higher levels and quality of environmental reporting (Rao et al, 2012;Liao et al, 2015;Ben-Amar et al, 2017;Lagasio & Cucari, 2019;Bravo and Reguera-Alvarado, 2019).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%